THE ROLE AND SIGNIFICANCE OF BILL OF LOADING IN DETERMINING THE CARRIER'S LIABILITY (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2023)
In the last decade of the 21st century, numerous and heterogeneous changes took place in the transport, forwarding and logistics sector. These changes were essentially a response to numerous and varies occurrences in the oil and energy industry, the world financial crisis, political conflicts and wars, as well as the emergence of the COVID-19 pandemic, which was perceived as a special challenge to this industry.From time perspective, nowadays, this sector has once again shown that adaptability is a strong point of this industry. Hence, its importance and role for the market of goods and services is more significant than ever before. Transportation per se is a challenge for explore from many aspects of the matter. From a legal point of view (which is our outstanding challenge), one of the most significant issues in the transport and logistics sector is the concept of “carrier liability”. From the position of an arbitrator and a judge, the most significant issue is the criteria, factors and evidentiary means for determining carrier’s liability.In this paper we will study the issue of the role and significance of transport documents in determining the carrier's liability, focusing both on the theoretical opinions and on the relevant practice, as a supplement to the theory and clearing up certain theoretical dilemmas that are still present.To achieve the goal, we will use the methods of analysis and synthesis, the method of description, the comparative method and the methods of induction and deduction. The latter in function of setting the summary, as a conclusion of the research.